Exame físico: opiniões e percepções de alunos de graduação em enfermagem - Angelo, Denise De Andrade Dias [UNESP] (1995)
This study aimed at getting to know the nursing graduate students' opnions and perceptions about concept of physical examination, difficulties, use of medicai information, as well as, the vision of teaching-Iearning process about the theme in questiono The authoresses concluded that: -the concepts expressed by them demonstrate the importance of behavior to the nursing assistance, diverging about to what evaluate; -the behavior is consider by themselves as always necessary for the nursing assistance, however, their difficulties are related to the lack of theorical-practical foundation, teachers not much prepared, limited time in the traineeships and lack of appropriate physical space for the executation of the behavior; -the theorical-pratical knowledge offered by the graduate courses aren't sufficient to the execution of the physical examinaton; -they show insecurity in the accomplishment of the physical examination, especially in the auscultation; -the students reveal that in spite of the physical exam result in exposing the patient the nurse must not be want to achieve it to the detriment of this to be carried out by other profissionais; -it' s said that they use medicai information for execution of the physical examination, however, this fact would need inquiries to explain which datas they are using and why use them.